White film and adhesive tape

JP2025034002APending Publication Date: 2025-03-13CHUKOH CHEM IND LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023140105
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0009】 本発明の実施形態によれば、耐摩耗性が高い白色フィルム、及び、この白色フィルムを含む粘着テープを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034002000001_ABST
    Figure 2025034002000001_ABST
Patent Text Reader

Abstract

To provide a white film and an adhesive tape having high wear resistance.SOLUTION: According to an embodiment, a white film is provided. The white film comprises polytetrafluoroethylene and zinc oxide particles.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a white film and an adhesive tape. [Background technology]

[0002] While polytetrafluoroethylene (PTFE) film has excellent properties such as chemical resistance, weather resistance, and high heat resistance, it has issues with abrasion resistance.

[0003] In order to impart advantageous properties to the PTFE film, fillers are added to the PTFE.

[0004] Patent Document 1, in relation to an ultraviolet blocking film, describes dispersing zinc oxide fine particles in polytetrafluoroethylene. It describes that in order to make the film transparent and have low ultraviolet transmittance, the particle size of the zinc oxide fine particles is set to 0.005 to 0.015 μm. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-173303 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a white film having high abrasion resistance, and a pressure-sensitive adhesive tape including this white film. [Means for solving the problem]

[0007] According to an embodiment, a white film is provided. The white film includes polytetrafluoroethylene and zinc oxide particles.

[0008] According to another embodiment, there is provided an adhesive tape including the white film according to the embodiment. Effect of the Invention

[0009] According to an embodiment of the present invention, it is possible to provide a white film having high abrasion resistance, and a pressure-sensitive adhesive tape including this white film. [Brief description of the drawings]

[0010] [Figure 1] 1 is a cross-sectional view illustrating an example of a pressure-sensitive adhesive tape according to an embodiment. [Diagram 2] FIG. 2 is a diagram illustrating an example of the shape of a zinc oxide particle. [Diagram 3] FIG. 13 is a perspective view illustrating an example of a thrust wear test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In order to impart abrasion resistance to polytetrafluoroethylene (PTFE) films, fillers are added to PTFE. Examples of fillers added to impart abrasion resistance include carbon black and carbon fiber. When such fillers are added, there is a problem that the color of the final product is limited to black to gray, which is the color of the filler. Other examples of fillers added to PTFE include inorganic pigments (for example, cobalt-aluminum composite oxide, which is a blue pigment). However, when such fillers are added, there is a problem that the color of the final product is derived from the pigment, and pinholes are likely to occur. In addition, when a sheet is formed by cutting a PTFE resin containing a pigment, the pigment may damage the blade used for cutting, which may cause chipping of the blade. There is a problem that chipping of the blade may cause scratches (bite scratches) on the sheet. Therefore, it is difficult to obtain a PTFE film that is highly abrasion resistant and white.

[0012] In addition, PTFE itself is milky white. Thin PTFE films are translucent milky white. Therefore, in order to obtain a white PTFE film, for example, it is necessary to add a white filler to PTFE.

[0013] However, sheets made by cutting and molding resin containing fillers tend to have pinholes, and there are issues with strength. Sheets with pinholes may break when pulled. For this reason, it is difficult to further stretch a sheet made by cutting and molding resin containing fillers to produce a film.

[0014] In addition, since PTFE film has high non-adhesiveness, it is difficult to adhere the PTFE film to materials such as adhesives. Therefore, when using the PTFE film as an adhesive tape, the film may be etched to improve the adhesion between the material such as adhesives and the film. However, since the film that has been etched turns brown, there is an issue that the color of the final product is limited to brown.

[0015] (First embodiment) According to an embodiment, a white film is provided that includes polytetrafluoroethylene and zinc oxide particles.

[0016] Zinc oxide particles are white in color. Furthermore, the abrasion resistance of a film containing zinc oxide particles can be improved. Therefore, a film containing zinc oxide particles can have high abrasion resistance and be white in color.

[0017] The white film according to the embodiment will be further described below.

[0018] The thickness of the white film is not particularly limited, but is, for example, within the range of 50 μm or more and 1000 μm or less. If the film is thick, the strength tends to be improved. For example, the film can be prevented from breaking when a pinhole occurs. If the film is thin, the flexibility tends to be improved. The thickness of the white film is preferably within the range of 50 μm or more and 300 μm or less.

[0019] In addition to polytetrafluoroethylene and zinc oxide particles, the white film according to the embodiment can optionally contain additives.

[0020] <Zinc oxide particles> The zinc oxide particles are particles containing zinc oxide. The ratio of the zinc oxide particles in the white film according to the embodiment can be, for example, 2% by mass or more and 20% by mass or less. The higher the ratio of the zinc oxide particles, the easier it is to obtain an effect of improving abrasion resistance. The lower the ratio of the zinc oxide particles, the more likely it is that the strength of the white film can be improved.

[0021] The shape of the zinc oxide particles is not particularly limited, but may be acicular, granular, etc. The zinc oxide particles are preferably acicular in shape.

[0022] The average particle size of the zinc oxide particles is preferably 100 μm or less, and more preferably 30 μm or less. The smaller the average particle size, the more likely it is that the dispersibility when mixed with PTFE can be improved. In addition, when a thin sheet is obtained by cutting, which will be described later, the smaller the average particle size, the more preferable it is. The average particle size of the zinc oxide particles can be, for example, 5 μm or more. The average particle size of the zinc oxide particles can be measured by observation with a transmission electron microscope (TEM).

[0023] The zinc oxide particles are preferably zinc oxide single crystals, more preferably acicular single crystals. The term "acicular" refers to a shape having an aspect ratio of 3 or more. The length of the acicular single crystal in the longitudinal direction may be, for example, 5 μm or more and 30 μm or less. The length of the acicular single crystal in the longitudinal direction may be called the fiber length.

[0024] The zinc oxide particles may have a three-dimensional structure in which a plurality of the above-mentioned needle-like single crystals are bonded together. For example, it is preferable that the zinc oxide particles have a shape in which four needle-like single crystals are bonded together in a tetrapod (registered trademark) shape. Even when the zinc oxide particles have a three-dimensional structure in which a plurality of the above-mentioned needle-like single crystals are bonded together, the average particle size of the zinc oxide particles can be the same as that described above.

[0025] An example of the shape of zinc oxide particles will be described with reference to FIG. 2. Zinc oxide particles 4 shown in FIG. 2 have a tetrapod-like shape. The tetrapod-like shape is, for example, as shown in FIG. 2, a shape in which four needle-like single crystals are integrated at one point and the longitudinal direction of each of the four needle-like single crystals extends toward the four vertices of a regular tetrahedron. It is considered that zinc oxide particles having such a shape can play a role of connecting molecular chains of polytetrafluoroethylene together. Therefore, the strength of the sheet obtained in the cutting described below can be increased, and a sheet that is less likely to break in the stretching process can be obtained. It is also considered that the anisotropy of polytetrafluoroethylene fibers can be reduced. In addition, a white film containing the zinc oxide particles can have high dimensional accuracy.

[0026] The fiber length of the needle-like single crystals of zinc oxide particles can be measured by TEM observation, and the shape of zinc oxide particles can also be identified by TEM observation.

[0027] <Additives> The white film may contain any additive. The type of additive is not particularly limited, but it is preferable that the additive is white or transparent in order to maintain the white color of the white film.

[0028] The proportion of the additive in the white film can be from 1% by mass to 30% by mass.

[0029] (Manufacturing method) The white film according to the embodiment can be produced, for example, as follows.

[0030] First, polytetrafluoroethylene and zinc oxide particles are mixed to obtain a mixture. The mixture may further contain an additive. The mixture is molded and pressed to obtain a billet. The billet may have a cylindrical shape, for example. The billet is fired and sintered in a firing furnace.

[0031] The sintered billet is cut to obtain a sheet. The cutting can be performed, for example, in a manner similar to that of a paper cutter. Cutting a cylindrical billet in a manner similar to that of a paper cutter is preferable because it is easy to obtain a long sheet with a uniform thickness. The thickness of the sheet can be appropriately changed depending on the desired film thickness, but can be, for example, about 0.1 mm. The obtained sheet may be wound up.

[0032] The sheet contains zinc oxide particles, which gives the sheet high strength and reduces the risk of pinholes, and therefore is less likely to break even when pulled, making it suitable for the stretching step described below.

[0033] The above-mentioned sheet is stretched in a heated state to obtain a white film. Heating can be performed, for example, at 327°C or higher, which is the melting point of PTFE. Stretching can be performed by uniaxially stretching the sheet in the length direction. Stretching can improve the tensile strength of the film, and the higher the stretch ratio, the more the tensile strength of the film tends to improve.

[0034] Second embodiment According to an embodiment, an adhesive tape is provided. The adhesive tape includes a substrate on a front surface and an adhesive layer on a back surface. The substrate is the white film according to the first embodiment.

[0035] The adhesive tape has the white film according to the first embodiment on the surface thereof, which provides high abrasion resistance.

[0036] The pressure-sensitive adhesive tape according to the embodiment will be further described below.

[0037] The thickness of the adhesive tape is not particularly limited, but may be, for example, within the range of 80 μm or more and 200 μm or less.

[0038] The adhesive tape may further include an intermediate layer interposed between the substrate and the adhesive layer. The intermediate layer includes silicon dioxide particles.

[0039] 1 is a cross-sectional view showing an example of an adhesive tape according to an embodiment. The Y-axis direction is parallel to the thickness direction of the adhesive tape. The X-axis direction is perpendicular to the Y-axis direction. The Z-axis direction is perpendicular to both the X-axis and Y-axis directions.

[0040] The adhesive tape 10 includes a substrate 1, an intermediate layer 2, and an adhesive layer 3. The substrate 1 is a white film according to the first embodiment.

[0041] The adhesive tape 10 has two main surfaces perpendicular to the Y-axis direction and aligned along the X-axis direction and the Z-axis direction. One of the two main surfaces is a front surface 11, and the other is a back surface 12. The adhesive tape 10 has a substrate 1 on the front surface 11 and an adhesive layer 3 on the back surface 12. The intermediate layer 2 is interposed between the substrate 1 and the adhesive layer 3.

[0042] <Base material> The substrate 1 is a white film according to the first embodiment.

[0043] The substrate 1 has two main surfaces perpendicular to the Y-axis direction and aligned along the X-axis and Z-axis directions. One of the two main surfaces of the substrate 1 is located on the surface 11 of the adhesive tape.

[0044] <Middle Class> The intermediate layer 2 may be laminated onto the substrate 1 .

[0045] An adhesive layer 3 is further laminated on the intermediate layer 2 laminated on the base material 1, so that the base material 1, intermediate layer 2, and adhesive layer 3 are laminated in this order along the Y-axis direction. As a result, the intermediate layer 2 is interposed between the base material 1 and the adhesive layer 3. FIG. 1 illustrates an example in which the intermediate layer 2 is laminated on the entire surface of one of the two main surfaces of the base material 1, but the intermediate layer 2 may be formed on at least a part of one of the main surfaces of the base material 1.

[0046] The intermediate layer 2 contains silicon dioxide particles. The intermediate layer 2 may further contain a fluororesin and an activator.

[0047] The silicon dioxide particles contained in the intermediate layer can reduce the non-adhesiveness of the main surface of the highly non-adhesive white film. Therefore, by having the intermediate layer 2 between the substrate 1 and the adhesive layer 3, peeling of the adhesive layer 3 from the substrate 1 can be suppressed.

[0048] In addition, the silicon dioxide particles are white. Therefore, even when the adhesive tape 10 includes the intermediate layer 2, the adhesive tape can maintain the white color of the white film according to the first embodiment. Therefore, peeling between the substrate 1 and the adhesive layer 3 can be suppressed without going through a process such as an etching process in which the white film, which is the substrate, is colored other than white.

[0049] The thickness of the intermediate layer 2 is not particularly limited, but is within the range of, for example, 1 μm or more and 30 μm or less.

[0050] The type of fluororesin contained in the intermediate layer 2 may be one type, or two or more types may be mixed.

[0051] When the intermediate layer contains a melt-flowable fluororesin, the fusion property between the substrate and the adhesive layer can be further improved. Here, the melt-flowable fluororesin is at least one selected from the group consisting of perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), and ethylene-tetrafluoroethylene copolymer (ETFE).

[0052] The silicon dioxide particles (SiO2) are preferably amorphous silica. More preferably, the amorphous silica is hydrophilic amorphous silica.

[0053] Silicon dioxide particles have a specific surface area of ​​10 m according to the Brunauer, Emmett, Teller (BET) adsorption isotherm. 2 / g or more. 2 By making the viscosity at 50 / g or more, the adhesion between the substrate and the adhesive layer can be improved. 2 / g or more 400m 2 / g or less.

[0054] The average primary particle size of the silicon dioxide particles is preferably in the range of 5 nm to 80 nm, more preferably in the range of 7 nm to 40 nm. The average primary particle size of the silicon dioxide particles can be measured by TEM observation.

[0055] The mass ratio of silicon dioxide particles to the mass of the intermediate layer is preferably in the range of 0.5% by mass or more and 30% by mass or less. By making this ratio 0.5% by mass or more, the adhesion between the substrate and the adhesive layer can be improved. If this ratio is increased, the adhesion between the substrate and the adhesive layer increases, but the brittleness of the intermediate layer increases, and the flexibility of the adhesive tape may decrease. By making this ratio 30% by mass or less, the adhesive tape has excellent flexibility. A more preferred range of this ratio is 5% by mass or more and 20% by mass or less.

[0056] The mass ratio of the fluororesin to the mass of the intermediate layer is, for example, within the range of 70 mass % to 99.5 mass %.

[0057] The intermediate layer may contain at least one surfactant selected from an anionic surfactant and a nonionic surfactant, for example. When the intermediate layer contains an surfactant, it has the effect of improving the leveling property and wettability.

[0058] <Adhesive layer> The adhesive layer 3 is a layer having adhesiveness. The form of the adhesive layer 3 is not particularly limited, and may be, for example, a layer containing an adhesive. The adhesive layer 3 may further contain a curing agent.

[0059] The thickness of the adhesive layer 3 is not particularly limited, but is, for example, in the range of 25 μm to 80 μm.

[0060] The adhesive may be, for example, at least one selected from a natural rubber adhesive, a silicone adhesive, and an acrylic adhesive. Among these, from the viewpoint of heat resistance, it is preferable that the adhesive contains a silicone adhesive and / or an acrylic adhesive.

[0061] Examples of silicone-based adhesives include peroxide-curing adhesives and addition-curing adhesives. When a peroxide-curing adhesive is used as the adhesive, at least one selected from the group consisting of benzoyl peroxide, dicumyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, and di-t-butyl peroxide can be used as the curing agent. When an addition-curing adhesive is used as the adhesive, platinum can be used as the curing agent.

[0062] <Manufacturing method> The pressure-sensitive adhesive tape according to the embodiment can be produced, for example, as follows.

[0063] (Formation of the intermediate layer) When producing a pressure-sensitive adhesive tape having an intermediate layer, an intermediate layer is formed on at least a part of one main surface of the white film according to the first embodiment as a substrate, for example, by the following method.

[0064] First, an aqueous dispersion containing a fluororesin and silicon dioxide particles is applied to one main surface of a white film as a substrate to form a coating film.

[0065] The aqueous dispersion contains at least water as a dispersion medium, and fluororesin and silicon dioxide particles dispersed in the water. The fluororesin is, for example, dispersed in the form of particles. The aqueous dispersion may further contain an activator. The aqueous dispersion contains, for example, silicon dioxide particles at a solid content concentration of 0.1% by mass or more and 20% by mass or less, and fluororesin at a solid content concentration of 1% by mass or more and 30% by mass or less.

[0066] After coating the aqueous dispersion, the coating may be dried as necessary, for example, by subjecting the coating to a temperature of 100° C. or less to evaporate the water content in the coating.

[0067] Thereafter, the coating film is baked. When the fluororesin contained in the aqueous dispersion is PFA resin particles, the baking can be performed at a temperature of, for example, 305°C or higher. The baking may be performed at a temperature equal to or higher than the melting point of the PFA resin, for example, within a range of 320°C to 340°C. The substrate may be further stretched at the same time as this baking process. By adding the stretching, the strength of the film can be further improved.

[0068] By the above-mentioned aqueous dispersion coating and baking steps, an intermediate layer can be formed on one main surface (one side) of the white film substrate.

[0069] <Formation of adhesive layer> The adhesive layer is formed according to a known method. When the intermediate layer is formed, the adhesive layer is formed on at least a part of the intermediate layer. When the intermediate layer is omitted, the adhesive layer is formed on at least a part of one main surface of the white film as the substrate.

[0070] The adhesive layer can be formed, for example, by preparing an adhesive-containing solution containing an adhesive and a curing agent, applying the solution onto the intermediate layer or one of the main surfaces of the substrate, and then heat-treating the solution. Examples of the solvent used for the solution include toluene and xylene.

[0071] The content of the curing agent in the adhesive-containing solution is, for example, in the range of 0.1% by mass to 15% by mass.

[0072] The viscosity of the solution for forming the adhesive layer is, for example, in the range of 1000 cP or more and 100,000 cP or less.

[0073] The adhesive is cured to form an adhesive layer by heat treatment following application of the adhesive-containing solution, which is carried out, for example, at a temperature in the range of 160° C. to 220° C. for a period of 120 to 600 seconds.

[0074] In this manner, an adhesive tape having a white film substrate on the front surface and an adhesive layer on the back surface can be manufactured. Since the adhesive layer is provided on only one side of this adhesive tape, it can be wound into a roll after the adhesive layer is formed. After the adhesive layer is formed, a release paper may be attached onto the adhesive layer. EXAMPLES

[0075] Adhesive tapes according to the examples and comparative examples were produced as follows.

[0076] Example 1 <Film Preparation> As polytetrafluoroethylene, PTFE molding powder M-18 manufactured by Daikin Industries, Ltd. was prepared. As zinc oxide particles, Panatetra (registered trademark) WZ-0501 manufactured by Koike Sangyo Co., Ltd. was prepared. The zinc oxide particles had an average fiber length of 10 to 20 μm and a particle shape of a tetrapod. Polytetrafluoroethylene was 90 mass % and zinc oxide particles were 10 mass % to produce a mixture. Next, the mixture was molded into a cylindrical shape and compressed under a compression pressure of about 18.5 MPa to produce a cylindrical billet. The billet was sintered in a sintering furnace at 370°C, which is a temperature higher than the melting point of PTFE. The sintered billet was cut using a cutting machine in a manner similar to wig peeling to obtain a sheet with a thickness of 0.108 mm. The obtained sheet was heated to about 365°C, and the sheet was uniaxially stretched to about 1.75 times in the heated state. Thus, a film having a thickness of 0.083 mm (83 μm) was obtained, the color of which was white.

[0077] <Formation of the intermediate layer> Next, an intermediate layer was formed on one of the main surfaces of the obtained film as follows. A dispersion liquid in which PFA resin particles and silicon dioxide particles were dispersed in water as a solvent was used. A nonionic surfactant manufactured by San Nopco Ltd. was prepared as an active agent. The ratios of the fluororesin particles, silicon dioxide particles, and active agent in the aqueous dispersion liquid were set to 4.8 mass%, 1.2 mass%, and 1.0 mass%, respectively. Using this aqueous dispersion liquid, an intermediate layer having a thickness of about 1 μm was formed on one of the main surfaces of the film by the method described above.

[0078] <Formation of adhesive layer> A silicone-based adhesive that cures with peroxide was prepared as the adhesive, and benzoyl peroxide was prepared as the curing agent. These adhesives and curing agents were dissolved in xylene as a solvent to prepare an adhesive-containing solution. This solution contained 50% by mass of the adhesive and 1% by mass of the curing agent relative to the mass of the solution.

[0079] This solution was applied onto the intermediate layer to form a coating film. The laminate with the coating film formed on the intermediate layer was placed in an electric oven and subjected to heat treatment while standing. This heat treatment was carried out at a temperature of 200°C for 280 seconds. Thus, an adhesive layer with a thickness of about 50 μm was formed. In this manner, the adhesive tape according to Example 1 was produced. The adhesive tape had a film substrate on the front surface and an adhesive layer on the back surface, and included an intermediate layer interposed between the substrate and the adhesive layer. The thickness of the produced adhesive tape was 0.1 mm.

[0080] Comparative Example 1 No zinc oxide particles were added when the mixture was produced. The billet after sintering was cut to produce a sheet having a thickness of 0.126 mm. The sheet was heated and uniaxially stretched in the same manner as in Example 1 to produce a film having a thickness of 0.099 mm (99 μm). The film was milky white in color. Except for the above, an adhesive tape having a thickness of 0.1 mm was produced in the same manner as in Example 1.

[0081] Comparative Example 2 When the mixture was produced, carbon black was mixed in place of zinc oxide particles. The film obtained in the film production was black. Except for the above, an adhesive tape having a thickness of 0.1 mm was produced in the same manner as in Example 1.

[0082] (Thrust wear test) The pressure-sensitive adhesive tapes according to the examples and the comparative examples were subjected to a thrust wear test as described below. The thrust wear test will be described with reference to Fig. 3. Fig. 3 is a perspective view that shows a schematic example of a thrust wear test.

[0083] First, the adhesive tape 10, whose mass had been measured in advance, was placed so that the back surface 12 was facing down and the front surface 11 was facing up. The SUS ring 5 was placed on the adhesive tape 10 so that the front surface 11 of the adhesive tape 10, i.e., the white film substrate, was in contact with the bottom surface of the SUS ring 5. The SUS ring used was a hollow cylindrical ring made of SUS304. The SUS ring had a bottom surface area of ​​2 cm2. 2 The following items were used.

[0084] A predetermined pressure was applied downward to the SUS ring 5, and only the adhesive tape 10 was rotated at a predetermined speed in the direction R shown by the arrow in Fig. 3, thereby causing friction between the bottom surface of the SUS ring 5 and the surface 11 of the adhesive tape 10. At this time, the center of the circle on the bottom surface of the SUS ring 5 and the center of rotation of the adhesive tape 10 were made to coincide.

[0085] After a certain period of friction, the mass of the adhesive tape was measured, and the difference in mass of the adhesive tape before and after friction was defined as the abrasion mass.

[0086] The wear test was performed twice by changing the friction conditions. For each Example and Comparative Example, the mass before friction, the mass after friction, and the wear mass are shown in Tables 1 and 2. Table 1 shows the results of the wear test performed under the conditions of a rotation speed of 0.5 m / s, pressure of 50 N, time of 10 minutes, and friction distance of 0.3 km. Table 2 shows the results of the wear test performed under the conditions of a rotation speed of 0.5 m / s, pressure of 10 N, time of 100 minutes, and friction distance of 3 km. The rotation speed is the rotation speed of the adhesive tape at the portion where the bottom surface of the SUS ring and the surface of the adhesive tape are in contact with each other.

[0087] [Table 1]

[0088] [Table 2]

[0089] (Physical property measurements for sheets and films) The cut sheets and stretched films in the manufacturing processes of Example 1 and Comparative Example 1 were each subjected to a tensile property test according to JIS-K-7137-2 to obtain strength (MPa) and elongation (%).

[0090] The measurement results are shown in Table 3. In Table 3, the cut sheet is shown as before processing, and the stretched film is shown as after processing. There was variation in the measurement results of strength (MPa) and elongation (%), so the range of values ​​is shown. Possible factors for the variation in values ​​include the billet formed in the film manufacturing process being a thick molded product, which means that heat is transferred differently between the outside and inside during sintering, and uneven filling of the filler.

[0091] [Table 3]

[0092] From the results of the thrust wear test, it was revealed that the pressure-sensitive adhesive tape of Example 1 had a lower wear mass and was superior in wear resistance than the pressure-sensitive adhesive tape of Comparative Example 1 not containing zinc oxide particles. Specifically, in the wear test results shown in Table 1, the wear mass of Comparative Example 1 was 3.3 times higher than that of Example 1. In the wear test results shown in Table 2, the wear mass of Comparative Example 1 was 9.6 times higher than that of Example 1. In other words, it was revealed that the wear resistance of Example 1 was 3.3 to 9.6 times higher than that of Comparative Example 1. The adhesive tape of Comparative Example 2 also had a low abrasion mass, but since it contained carbon black, the color of the film was black, and the color of the adhesive tape was also black.

[0093] From the results of measuring the physical properties of the sheet and film, the film of Example 1 tended to have a greater elongation to break both before and after the treatment than the film of Comparative Example 1. Therefore, it was revealed that the film of Example 1 had a higher strength against breakage due to tension than Comparative Example 1.

[0094] Therefore, it has become clear that the embodiment can provide a film that is highly abrasion resistant and white in color, and an adhesive tape that includes the white film.

[0095] The present invention is not limited to the above-mentioned embodiment, and can be modified in various ways without departing from the gist of the present invention. The embodiments may be combined as appropriate, and in that case, the combined effect can be obtained. Furthermore, the above-mentioned embodiment includes various inventions, and various inventions can be extracted by combinations selected from the multiple components disclosed. For example, if the problem can be solved and the effect can be obtained even if some components are deleted from all the components shown in the embodiment, the configuration from which the components are deleted can be extracted as an invention. [Explanation of symbols]

[0096] 1...base material (white film), 2...intermediate layer, 3...adhesive layer, 4...zinc oxide particles, 5...SUS ring, 10...adhesive tape, 11...surface, 12...back surface.

Claims

1. A white film comprising polytetrafluoroethylene and zinc oxide particles.

2. The white film according to claim 1 , wherein the zinc oxide particles have an average particle size of 5 μm or more and 100 μm or less.

3. An adhesive tape having a substrate on a front surface and an adhesive layer on a back surface, 3. An adhesive tape, wherein the substrate is the white film according to claim 1 or 2.

4. Further comprising an intermediate layer interposed between the substrate and the adhesive layer; The adhesive tape of claim 3 , wherein the intermediate layer comprises silicon dioxide particles.

Citation Information

Patent Citations

  • Ultraviolet-screening film and its production

    JP1995173303A